The Bruce Collection of Eskimo material culture from Port Clarence, Alaska / Fieldiana, Anthropology, v. 67 - VanStone, James W. ([Chicago] : Field Museum of Natural History, 1976)
Includes bibliographical references (p. 58-59). Fieldiana series has been published as Anthropological Series by Field Columbian Museum (1895-1909) and Field Museum of Natural History (1909-1943), and as Fieldiana: Anthropology by Chicago Natural History Museum (1945-1966) and Field Museum of Natural History (1966-).